The effect of individual characteristics on organizational citizenship behavior (OCB) with intrinsic motivation as an intervening variable in BUMDES - Epsilandri Setyarini; Muhammad Hengki Setiawan (Journal of Business Studies and Management Review, 2020)
BUMDes Panggung Lestari in Sewon, Bantul currently still lacks in development. Even if BUMDes Panggung Lestari has a fairly large tracts of land, it cannot be utilized optimally due to inadequate human resources and lack of vision and missions of the organization to develop the economy of the community members of Panggungharjo Village, creating uneven economic development. This study aims at determining the factors affecting OCB in BUMDes Panggung Lestari in Panggungharjo Village, Sewon District, Bantul Regency. On the other hand, this study also aims at enabling BUMDes Panggung Lestari to improve the quality of its human resources to become a pioneer for other BUMDes. The sampling method used in this study was accidental sampling with 82 respondents. The analytical methods used in this study were T-test and Sobel test. The results of the study showed that individual characteristics have a significant, positive effect on OCB with a significance value of 0.000, the individual characteristic has a significant effect on intrinsic motivation with a significance value of 0.005, and intrinsic motivation has a positive effect on OCB with a significance value of 0.000. OCB with intrinsic motivation as an intervening variable has a significance value of 0.013. It is expected that this study can be used to measure individual characteristics and intrinsic motivation for OCB.